2007
DOI: 10.1590/s0100-40422007000200026
|View full text |Cite
|
Sign up to set email alerts
|

Plantas medicinais: fatores de influência no conteúdo de metabólitos secundários

Abstract: . do Café, s/n, 14040-903 Ribeirão Preto -SP, BrasilRecebido em 7/7/05; aceito em 11/4/06; publicado na web em 31/10/06 MEDICINAL PLANTS: FACTORS OF INFLUENCE ON THE CONTENT OF SECONDARY METABOLITES. Since secondary metabolites represent a chemical interface between plants and surrounding environment, their syntheses are frequently affected by environmental conditions. Thus, variations in the total content and/or of the relative proportions of secondary metabolites in plants can take place. We review the main … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

13
364
5
158

Year Published

2008
2008
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 913 publications
(591 citation statements)
references
References 136 publications
13
364
5
158
Order By: Relevance
“…It is known that specimens of the same species can be different in terms of the presence of one or more classes of chemical constituents over time and space, and that these variations can be seasonal or daily and can occur intraplant or interplant [6]. The diversity of chemical components can be due to a number of factors, such as climate and the action of herbivores [6][7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…It is known that specimens of the same species can be different in terms of the presence of one or more classes of chemical constituents over time and space, and that these variations can be seasonal or daily and can occur intraplant or interplant [6]. The diversity of chemical components can be due to a number of factors, such as climate and the action of herbivores [6][7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…The diversity of chemical components can be due to a number of factors, such as climate and the action of herbivores [6][7][8][9][10]. However, most studies on the chemical variability of plants have been limited to commercially important species that may have suffered pressure from the search for certain characteristics desired by humans.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In the present study, we observed a low yield of essential oil in comparison with previous research . These differences in chemical composition and essential oil yield between samples from different studies occur by several factors, such as the biotic and abiotic factors of the geographic regions where the specimens are found, genetic characteristics, season in which the plant was collected, and plant growth and development (Gobbo- Neto & Lopes, 2007).…”
Section: Qualitative Analysis Of the Essential Oilmentioning
confidence: 99%